Childhood as historical subjects in school content related to state terrorism: an analysis of the practices and representations of secondary school teachers and students (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
The purpose of this article is to share a preliminary overview of the results of a research project conducted to analyze the place of childhood as historical subjects in secondary school history classes (in general) and, on this occasion, based on the selection of a specific subject: the last military dictatorship in Argentina. Based on this, it can be said that, in general, and although research on recent history and the ways in which children have experienced the last military dictatorship in Argentina has been growing, these productions have had little impact (yet) on school content, the production of educational materials, and benchmark school practices. Furthermore, the investigation into teachers' and students' representations of the topic has also revealed a disparity in intentions and interests regarding its possible approaches.
Keywords: History teaching; childhood; dictatorship